The Immorality of a Husband as the Cause of a Working Wife to File for Divorce Lawsuit in Indonesia - Jumni Nelli; Afrizal Mansur; Zulkifli Zulkifli; Maghfirah Maghfirah; Sofia Hardani; Izzah Nur Aida (Institut Agama Islam Negeri Batusangkar, 2023)
This research aimed at finding out the meaning of a divorce suit for a working wife and to prove that economic problems caused by the husband’s immorality are the reason a working wife files a divorce suit. The data sources in this study were documentation and interviews with 13 wives who filed for divorce at Pekanbaru Religious Court in 2019-2020, Indonesia. Alfred Schutz’s phenomenological method of “because to” motive and “In order to” motive was used to analyse the data. The results of the study shows that the reason for “because to” motive was the husbands’ immorality. Meanwhile, the reasons for “In order to” motive were (a) Getting out of the burden of conflict. (b) Getting out of household economic pressure (c) Clarity of status and (d) Freeing oneself from deceit and slander. It can be understood that the meaning of divorce for a working wife for economic reasons is the distribution of emotions of dissatisfaction with the husband’s attitude; escape from physical and mental suffering; freedom; and failure to respect each other. The implications of this research can be used to generalize divorce cases on the grounds of husband’s immorality in Indonesia.